Central banking in practice : some experiences from Trinidad and Tobago - Forde, Penelope ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1998)
Examines the relationship between the central bank and the government, at the heart of which lies the question of the independence of the central bank and its meaning in a Caribbean context. Looks at a new policy instrument, the use of open market operations.